Land Rights and Economic Development : Evidence from Vietnam - Do, Quy-Toan; Iyer, Lakshmi (World Bank, Washington, DC, 2014)
The authors examine the impact of land reform in Vietnam which gives households the power to exchange, transfer, lease, inherit, and mortgage their land-use rights. The authors expect this change to increase the incentives as well as the ability to undertake long-term investments on the part of households. Their difference-in-differences estimation strategy takes advantage of the variation across provinces in the issuance of land-use certificates needed to enforce these rights. The results indicate that the additional land rights led to significant increases in the share of total area devoted to multi-year crops, as well as some increase in irrigation investment. These effects are stronger in areas that felt the impact of the land reform earlier.